First record of the genus Caenophanes Foerster (Hymenoptera: Braconidae: Doryctinae) for America north of Mexico with a description of a new species from Wyoming USA - Haimowitz, Lawrence; Marsh, Paul M.; Shaw, Scott R. (Zootaxa, 2014)
The first species of Caenophanes Foerster recorded from America north of Mexico is described: Caenophanes harlowi Haimowitz and Marsh, and a key to distinguish the two described New World species is provided. We discuss evidence that suggests that Caenophanes is likely to have cosmopolitan distribution and may be more common than might be anticipated from the current number of described species.